Efficacy of teaching creative thinking skills: A comparison of multiple creativity assessments. (June 2017) - Perry, Anna; Karpova, Elena
Highlights: Belief in creative abilities increased most after training. As a group, participants significantly increased their creativity after training. Several students demonstrated a decrease in creative abilities after training. Regression to the mean explained why participants decreased in creativity. Abstract: The purpose of this study was tri-fold: (1) to evaluate the efficacy of a creative thinking course using three different assessments; (2) to analyze changes in creativity as a result of the training for individual participants; and (3) to investigate reasons for individual decreases in creativity after the training. Data was collected at the beginning and the end of a creative thinking course at a large land-grant Midwestern university. After the course, students had the most significant increase in belief in their own creative abilities, followed by an increase in attitude toward risk-taking, and creative thinking evaluated by experts. While as a group, participants had significantly increased their creative abilities, several of them demonstrated a decrease in creative abilities after the course. A statistical phenomenon, regression to the mean, was employed to explain why some participants demonstrated lower creative thinking after completing the course.